PENDAMPINGAN PENYUSUNAN STANDAR OPERASIONAL PROSEDUR PELAYANAN KEPEMILIKAN HAK ATAS TANAH DI DESA PILOHAYANGA KECAMATAN TELAGA KABUPATEN GORONTALO - Tome, Abdul Hamid; Dungga, Weny A; Wantu, Fence M; Puluhulawa, Mohamad Rusdiyanto U; Ismail, Dian Ekawaty; Puluhulawa, Irlan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This service activity focuses on assisting in the preparation of Standard Operating Procedures (SOP) for land ownership services in Pilohayanga Village, Telaga District, Gorontalo Regency. The background to this activity is that there are obstacles in the process of issuing letters of release of land rights caused by the absence of standard SOPs in the village. Through observation, interviews and participatory workshops, this activity aims to increase understanding of village officials and the community regarding regulations and appropriate administrative mechanisms for releasing land rights. A participatory approach in preparing SOPs ensures that local needs are properly accommodated, so that the final product is more relevant and effective in addressing existing problems. The results of the activity show an increase in village officials' understanding of correct administrative procedures and commitment to implementing the prepared SOPs. Thus, this activity not only produces clear technical guidance, but also strengthens government governance at the village level, especially in the aspect of transparent and accountable public services.